2021
DOI: 10.33233/rbfe.v18i4.3237
|View full text |Cite
|
Sign up to set email alerts
|

Estereologia e morfometria do tecido muscular-esquelético de animais submetidos a um programa de treinamento de força e suplementação de creatina durante 9 semanas

Abstract: A creatina pode promover efeitos ergogênicos na prática do exercício físico de alta intensidade, entretanto, são encontradas poucas evidências que relatam a respeito dos efeitos morfométricos e estereológicos da associação desses componentes em modelos experimentais. Para isso, foram selecionados 24 ratos Wistar que se encontravam com idade de 15 semanas e estavam sob condições de alimentação e hidratação controladas. Para verificar as modificações morfométricas e estereológicas foi feita a classificação dos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…supplement only without concomitant training. In this sense, the results observed in this study corroborate the observations already available in the scientific literature [17,19,23] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…supplement only without concomitant training. In this sense, the results observed in this study corroborate the observations already available in the scientific literature [17,19,23] .…”
Section: Discussionsupporting
confidence: 92%
“…between resistance training series [14] . Also, in another study, tissue morphometry was observed after creatine use in association with training [19] . Results indicated nuclear and sarcoplasmic morphometric differences for trained and supplemented animals when compared to only supplemented or only trained animals [19] .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations